2020
DOI: 10.1001/jamaoto.2019.3969
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vocal Fold Immobility After Prolonged Endotracheal Intubation

Abstract: and mechanical ventilation are life-saving treatments for acute respiratory failure but are complicated by significant rates of dyspnea and dysphonia after extubation. Unilateral vocal fold immobility (UVFI) after extubation can alter respiration and phonation, but its incidence, risk factors, and pathophysiology remain unclear.OBJECTIVES To determine the incidence of UVFI after prolonged (>12 hours) mechanical ventilation in a medical intensive care unit and investigate associated clinical risk factors for UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Prone positioning was a factor that was significantly different between the two groups. It has been suggested that UVFI after endotracheal intubation is caused by recurrent laryngeal nerve paralysis (RLNP) due to compressive neural injury or arytenoid dislocation/subluxation 14,20,21 . It was difficult to differentiate between these two diseases because we did not perform laryngeal electromyography.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Prone positioning was a factor that was significantly different between the two groups. It has been suggested that UVFI after endotracheal intubation is caused by recurrent laryngeal nerve paralysis (RLNP) due to compressive neural injury or arytenoid dislocation/subluxation 14,20,21 . It was difficult to differentiate between these two diseases because we did not perform laryngeal electromyography.…”
Section: Discussionmentioning
confidence: 96%
“…Our results, which demonstrated UVFI in approximately 30% of patients, were consistent with these previous reports. The reported incidence of UVFI after prolonged intubation ranges from 7% to 41% among patients without COVID‐19 14–17 . However, it has not previously been reported whether there is a difference in the frequency of UVFI between COVID‐19 and other diseases requiring endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative laryngeal complications could be a result of direct or indirect trauma to the vocal cords causing edema, hematoma, or nerve stretch 18 . For the first time, our study provided significant direct objective evidence, that intubation will lead to laryngeal inflammation, which decreased the glottic area and vocal angle and increased the vocal fold width and area.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma during endotracheal intubation could cause post-operative laryngeal complications with vocal cords edema or hematoma ( 13 ). Inflammation changes the tissue composition leading to higher water content and edema leads to significant changes in laryngeal mucosal thickness, including decreases the glottic area and vocal angle and increases the vocal fold width and area.…”
Section: Discussionmentioning
confidence: 99%